Cost of detecting gastric neoplasia by surveillance endoscopy in atrophic gastritis in Italy: A low risk country. Issue 3 (March 2017) - Lahner, Edith; Hassan, Cesare; Esposito, Gianluca; Carabotti, Marilia; Zullo, Angelo; Dinis-Ribeiro, Mario; Annibale, Bruno
Abstract: Background: Atrophic gastritis (AG) is at increased risk of gastric neoplasia, thus surveillance gastroscopy has been proposed. Aims: To assess cost of detecting gastric neoplasias by surveillance endoscopy according to identified risk factors in Italy. Methods: Post-hoc analysis of a cohort study including 200 AG-patients from Italy followed up for a mean of 7.5 (4–23.4) years was done. Considered risk factors were: age >50 years, extensive atrophy, pernicious anaemia, OLGA-OLGIM scores 3–4 at diagnosis. The number of 4-year-surveillance endoscopies needed to be performed to detect one gastric neoplasia (NNS) was calculated. Results: In 19 patients neoplasias (4 gastric cancers, 8 type 1 gastric carcinoids, 7 dysplasias) were detected at the 361 surveillance gastroscopies, corresponding to NNS of 19 and a cost per gastric neoplastic lesion of €2945. By restricting surveillance to pernicious anaemia patients, reduction of NNS and cost per neoplasia to 13.8 and €2139 may be obtained still detecting 74% of neoplasias. By limiting the surveillance to pernicious anaemia patients and OLGA 3–4, 5 (26.3%) neoplasias would have been detected with a corresponding NNS of 5.4 and a cost per lesion of €837. Conclusion: Risk factors may allow an efficient allocation of financial and medical resources for endoscopic surveillance in AG in a low risk country.